HUBUNGAN EFEKTIVITAS KOMUNIKASI ORGANISASI DAN KUALITAS LAYANAN TERHADAP KEPUASAN MITRA LEMBAGA PENYIARAN PUBLIK (LPP) TVRI SUMATERA BARAT - Adlen, Adlen; Jendrius, Jendrius; Kohar, Wakidul (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
The success of an organization can be measured by the level of satisfaction felt by partners/clients. Basically, many factors that influence the level of satisfaction of partners/clients include the effectiveness of communication and service quality. In the past few years TVRI Sumatra has experienced a decline in the number of customers. This may be caused by the effectiveness of communication and poor service quality. This type of research is quantitative using analytic descriptive design. Sampling was determined by the total sampling technique on TVRI West Sumatra Public Broadcasting Partners, which amounted to 67 respondents. Data collection tools using questionnaires and observations. Data analysis using Chi-square. The results showed that there was a significant relationship between the effectiveness of organizational communication with Partner Satisfaction with a P value of 0,000 (P <0.05) OR 7,500 (95% CI = (2,533-22,204), and there was a significant relationship between service quality and satisfaction partners with a SE value of a value of OR 37,500 (95% CI = (7,509-187,284).